One-step synthesis of SBA-15 containing tungsten oxide nanoclusters: a chemoselective catalyst for oxidation of sulfides to sulfoxides under ambient conditions - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Chemical Communications, 2007)
Tungsten oxide nanoclusters supported highly ordered mesoporous SBA-15 material has been successfully synthesized in a single step using a non-ionic surfactant as a template and used for the selective oxidation of sulfur compounds, giving excellent yields at room temperature with exceptional catalyst recyclability.